A study on public perception and attitudes towards electronic waste management in Singapore - Wong, Jing Jing (2025)
Electronic waste (e-waste) is a growing environmental challenge worldwide, particularly in highly urbanized nations like Singapore, where rapid technological advancements and high consumer demand contribute to increasing volumes of discarded electronic products. This study examines public perceptions, attitudes, and behaviors toward e-waste management in Singapore, focusing on the influence of demographic factors, psychological determinants, and educational interventions. Using a quantitative research approach, the study finds that demographic factors have a limited impact on e-waste management behaviors, while psychological factors show no significant influence, underscoring the complexity of translating positive attitudes into actionable behaviors. Educational interventions demonstrate moderate effectiveness in promoting responsible smartphone disposal but have a limited impact on other e-waste behaviors. These findings highlight the need for a multifaceted approach to e-waste management, integrating improved infrastructure, targeted educational campaigns, and policy support to bridge the gap between awareness and action. Key recommendations include enhancing accessibility to e-waste recycling facilities, expanding school-based and community education programs, and leveraging social norms to foster a culture of environmental responsibility. This study provides valuable insights for policymakers, industry stakeholders, and environmental advocates seeking to strengthen e-waste management frameworks in Singapore and beyond.